2014
DOI: 10.5301/ijao.5000290
|View full text |Cite
|
Sign up to set email alerts
|

Are Serum to Dialysate Sodium Gradient and Segmental Bioimpedance Volumes associated with the Fall in Blood Pressure with Hemodialysis?

Abstract: Falls in blood pressure are common during dialysis, and greater for those starting dialysis with the highest systolic pressures, greater dialysate to serum sodium concentration gradient, and also those with the least ECW in the arm. As such, segmental bioimpedance may be useful in highlighting patients at greatest risk for a fall in blood pressure with dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Our findings are consistent with the current literature demonstrating a positive correlation between the sodium gradient and parameters of fluid overload in hemodialysis patients [15, 16, 19–21, 23, 27, 28]. These associations of a high sodium gradient with fluid overload are likely explained by a high dialysate sodium concentration leading to an elevated postdialysis serum sodium level with the consequence of increased thirst and fluid intake [29].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the current literature demonstrating a positive correlation between the sodium gradient and parameters of fluid overload in hemodialysis patients [15, 16, 19–21, 23, 27, 28]. These associations of a high sodium gradient with fluid overload are likely explained by a high dialysate sodium concentration leading to an elevated postdialysis serum sodium level with the consequence of increased thirst and fluid intake [29].…”
Section: Discussionsupporting
confidence: 92%
“…The median follow-up was 19 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) months. During the first 12 months, 77 patients died (11%) and 55 were transplanted (8.3%).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study reported that intradialytic hypotension was a major difference between those who required time to recover postdialysis compared to those who needed no recovery time, 9 and greater cardiovascular stability during HD has been reported to reduce recovery time. 5,25 We only recorded the predialysis and postdialysis blood pressures of a single dialysis session, at the time of the questionnaire. We accept that changes in blood pressure may vary during the dialysis week, and from week to week.…”
Section: Discussionmentioning
confidence: 99%
“…However, IDH is probably multifactorial. Unfortunately, available data precluded study of the effects of dialysis sodium concentration and dialysate temperature, both of which may also affect IDH (21). Furthermore, prior studies indicate that fluid status with respect to extracellular euvolemia may be an important determinant in IDH (22,23).…”
Section: Discussionmentioning
confidence: 99%